2017
DOI: 10.1634/theoncologist.2016-0193
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab in Human Epidermal Growth Factor Receptor 2-Positive Early Breast Cancer: Results of a Prospective, Noninterventional Study on Routine Treatment Between 2006 and 2012 in Germany

Abstract: Purpose. Trastuzumab is part of the standard treatment in patients with human epidermal growth factor receptor 2-positive early breast cancer in addition to (neo)adjuvant chemotherapy. This German prospective noninterventional study, which included major patient cohorts underrepresented in the pivotal randomized studies, examined the generalizability of the results of those studies. Patients and Methods. Between 2006 and 2012, 4,027 patients were enrolled and treated with trastuzumab; they were unselected rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…However, the general recommendations for heart function assessment were not followed in a considerable number of patients. The rate of patients having echocardiography was only around 60% per three-month time interval [ 14 ]. Other presumed adverse drug reactions of severity grade 3/4 were rare in the monotherapy group: two cases of cardiac arrhythmia, two cases of dyspnea or other lung toxicity, and one patient with elevated liver enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the general recommendations for heart function assessment were not followed in a considerable number of patients. The rate of patients having echocardiography was only around 60% per three-month time interval [ 14 ]. Other presumed adverse drug reactions of severity grade 3/4 were rare in the monotherapy group: two cases of cardiac arrhythmia, two cases of dyspnea or other lung toxicity, and one patient with elevated liver enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the organizational and legal framework of this non-interventional study (Roche ML20315), the selection criteria for inclusion in the observation procedure, and the scope of the documentation have been described previously [ 14 ]. In general, patients were treated and their disease course was assessed according to routine practice at the treating institution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the included patient subgroups were not commonly presented in phase III trials (e.g., elderly patients and patients with stage I disease). The overall survival rates at 3 and 5 years seem to confirm the advantage conferred by trastuzumab use in eBC [26].…”
Section: Real World Effectivenessmentioning
confidence: 98%
“…In the trastuzumab arms of the BCIRG-006 (Breast Cancer International Research Group 006) trial, 25% of patients eventually developed a 10-year DFS event (30% in case of LN+ disease) [5]. Moreover, it has been observed that pathological primary tumor size, LN involvement, and hormone receptor status have the greatest independent effect on recurrence risk [6].…”
mentioning
confidence: 99%